Effect of dental base metal alloys on IgE levels and some blood parameters - ÖZKAN, YASEMİN (Blackwell Publishing Ltd, 1997)
Despite the widespread use of nickel-based alloys, claims for safety of these alloys have not yet been accepted universally. The allergenic effects of nickel on dental patients and the potential toxic effects of nickel and beryllium on laboratory technicians continue to cause concern within the dental profession. The purpose of this study was to investigate immunoglobulin type E (IgE) values and some blood parameters of dental laboratory technicians who use dental base metal alloys. The following two groups were studied: 19 students who had been working with dental base metal alloys for two years; and 21 pre-clinical students who had never worked with dental base metal alloys. The latter group were used as a control. Blood specimens were taken from both groups and analysed using The Blood Counter. Total erythrocyte, thrombocyte, leukocyte, lymphocyte, granulocyte and monocyte counts were determined. Measurement of IgE was made with Coat-A-Count Total IgE IRMA. Blood and IgE measurements were repeated after 8 months. In the experimental group both erythrocyte and thrombocyte values were found to be statistically significantly decreased compared with the control group. No significant differences were found in lymphocyte and monocyte numbers between the initial and later measurements. There were no significance changes in IgE values for both groups. These results provide no evidence that dental base metal alloys (Ni, Cr, Be, Co) caused an increase in sensitization, during the period of the study. © 1997 Blackwell Science Ltd.